2011
DOI: 10.1590/s0101-20612011000400017
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic behavior of buriti (Mauritia flexuosa) fruit

Abstract: Foram caracterizadas a casca, a polpa e a parte fibrosa do buriti (Mauritia flexuosa) e avaliados os seus comportamentos higroscópicos, visando estabelecer condições de secagem e de armazenamento para os produtos. Foram obtidas isotermas de adsorção e dessorção de umidade a 25 °C, determinado o valor da monocamada e avaliada a aplicabilidade dos modelos: Halsey, Handerson, Kuhn, Mizrahi, Oswin, Smith, BET e GAB, na predição das isotermas. A polpa foi classificada como rica em óleo de alta qualidade e juntament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…Buritis from the Cerrado presented higher moisture when compared to those from the Amazon region and to those reported for buritis collected in areas located in the Cerrado and Amazon biomes or the transition between the two (Melo et al, 2011). This diversity of results may be related to factors such as the commonly employed method of pulping the fruit, which involves water immersion, in addition to environmental factors inherent to climatic and geographic conditions.…”
Section: Composition In Nutrients and Caloric Valuementioning
confidence: 71%
See 1 more Smart Citation
“…Buritis from the Cerrado presented higher moisture when compared to those from the Amazon region and to those reported for buritis collected in areas located in the Cerrado and Amazon biomes or the transition between the two (Melo et al, 2011). This diversity of results may be related to factors such as the commonly employed method of pulping the fruit, which involves water immersion, in addition to environmental factors inherent to climatic and geographic conditions.…”
Section: Composition In Nutrients and Caloric Valuementioning
confidence: 71%
“…Buriti oil is an interesting alternative source of tocopherol, carotenoids and monounsaturated fatty acids (Melo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Type-OO behavior was observed by Torres et al (2012) for adsorption isotherms of carboxymethyl cellulose, guar gum, locust gum, tragacanth gum, and xanthan gum at different temperatures (20-65 °C). Melo et al (2011) also observed type-OO sorption isotherms for the skin, pulp, and fibrous part of buriti (Mauritia flexuosa).…”
Section: Bg Sorption Isothermsmentioning
confidence: 74%
“…Rosa e cv. Tommy Atkins e Melo et al (2011) em polpa de buriti; o segundo melhor ajuste foi obtido pelo modelo de BET seguido dos modelos de Oswin e Henderson (Tabela 2). De acordo com Andrade et al (2011) o modelo de BET é aplicável entre atividades de água de 0,05 e 0,45 porém neste trabalho se obtiveram bons resultados para toda a faixa de atividade de água aplicada.…”
Section: Resultsunclassified